Internet das coisas: uso de sensores e atuadores na automação de um protótipo residencial - Longo, Lucas (2015)
Nowadays much is said about an innovative concept that basically says that all objects used in daily life will be connected to the Internet and the information provided by these objects will be accessed directly via a single IP, each object will be able to obtain information from the environment and interact according to the obtained data. This concept takes the name Internet of Things. These objects and systems uses sensors and actuators to make interaction with the environment. In this work a system for home automation will be developed, in this study the home is seen as an Internet of Things object. The connection of the Internet will be made using a Web server installed in a Raspberry Pi. The user is able to choose the actions of the actuators or even put in automatic mode. These actions are sent to the microcontroller, responsible for activating the actuators in the system through communication via radio frequency. Besides being responsible for actuators microcontroller also reads the sensors used to automatic actuators, the data is also sent to the central through communication via radio frequency, this data is displayed for the user so he can make decisions. In addition, user access interface is responsive, which means that the interface is able to adapt to any device that have Internet access. The user can access the control interface of his home from anywhere with Internet connection.